Medium-term plan 2002-2006 : focused on people and committed to the future (IICA San JoseCR, 2002)
Sets out the intended direction and course of action for the Institute for the period 2002-2006. Reflects on the mandates from the Third Summit of the Heads of State and Government of the Americas as contained in the Summit's Declaration and Plan of Action, and the Bavaro Declaration of the Ministers of Agriculture, in their first Ministerial Meeting on Agriculture and Rural Life held in the Dominican Republic in 2001.
Keywords: AGRICULTURAL PLANNING